Income Inequality, Redistribution of Income and Trade Openness (The Pakistan Development Review, 2015)
Literature on nexus between trade openness and government spending is impressive [Atif, et al. (2012), Rudra (2004), Dani (1997) and McGuire (1999)]. The literature is growing rapidly. Analysts have documented the positive effects of government social spending [see for example Mesa-Lago (1994); Huber (1996); Weyland (1996); McGuire (1999)]. Unfortunately, Pakistan lacks empirical evidences on the impact of government social spending. Although Government of Pakistan has taken number of initiatives to have some form of redistribution policies, however, inequality in Pakistan is higher as compared to other Least Developed Countries that are open to trade. This situation is alarming. This paper therefore tries to identify the nexus between trade openness and social spending for the period 1975–2012. International evidence suggests that government social spending influences poverty and distribution of income. Pakistan‘s low level achievement in terms of reducing inequality, given the likely adverse economic impact of trade openness, point towards the fact that government has to design the policy in such a way that it affects the distribution of income. Thus, exploring the effect of social spending on income inequality is necessary for the concerned policy makers.